Musik für Kinder; Lieder und Klavierstücke (1974)
Seite 1:<NZ>Lieder und Klavierstücke von Hanns Eisler, Rudolf Wagner-Régeny, Günter Kochan, Paul Dessau, Fidelio F. Linke, Leo Spies, Jürgen Wilbrandt, Ernst Hermann Meyer, Kurt Schwaen.<NZ>Seite 2:<NZ>Lieder und Klavierstücke von Günter Kochan, Kurt Schwaen, Siegfried Köhler, Leo Spies, Fritz Geisler.;